KONSEP PENDIDIKAN QUR’ANI: INTEGRASI NILAI SPIRITUAL, MORAL, DAN TEKNOLOGI DALAM PEMBELAJARAN MODERN - Abdul Razzaq; Nurcholis Aziz; Yuspiani; Alwan Subhan (Pascasarjana IAIN Sorong, 2026)
This study aims to explore educational values ​​in the Quran, Quranic learning methods, and their relevance to modern learning theories. Using a descriptive qualitative approach based on literature review, this article analyzes Quranic verses related to educational concepts, such as Surah Al-Baqarah, Surah Ali Imran, Surah Yusuf, Surah An-Nahl, and Surah Al-Mulk, as well as interpretations by scholars such as M. Quraish Shihab, Jalaluddin Al-Mahalli, and Ibn Kathir. The results show that the Quran offers a holistic learning method that includes parables, stories, targhīb-tarhīb, dialogue, role models, practical exercises, and advice. These methods align with modern learning theories, such as Behaviorism, Constructivism, and Experiential Learning. Another finding of this study is that the integration of technology in Islamic education can be achieved by considering Quranic values, such as lite racy, information validation, trustworthiness, and digital etiquette. Quranic education can address the challenges of the modern era by integrating intellectual, spiritual, moral, and social dimensions.